2003
DOI: 10.1002/cne.10985
|View full text |Cite
|
Sign up to set email alerts
|

Types of bipolar cells in the mouse retina

Abstract: We studied the morphology of bipolar cells in fixed vertical tissue sections (slices) of the mouse retina by injecting the cells with Lucifer Yellow and Neurobiotin. Nine different cone bipolar cell types and one rod bipolar cell type were distinguished. The major criteria for classifying the cells were the branching pattern and stratification level of their axon terminals in the inner plexiform layer (IPL). To assess this, the IPL was subdivided into five strata of equal width. The slices were immunostained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
419
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(454 citation statements)
references
References 63 publications
28
419
1
6
Order By: Relevance
“…These CBCs, referred to as CB2 in this study, should undoubtedly correspond to type 3 CBCs that have been described both in rats (Euler & Wässle, 1995;Hartveit, 1997) and in mice (Ghosh et al, 2004;Pignatelli & Strettoi, 2004;Ivanova & Müller, 2006).…”
Section: Two Types Of Cbcs Expressing Voltage-gated Na + Channelssupporting
confidence: 51%
See 1 more Smart Citation
“…These CBCs, referred to as CB2 in this study, should undoubtedly correspond to type 3 CBCs that have been described both in rats (Euler & Wässle, 1995;Hartveit, 1997) and in mice (Ghosh et al, 2004;Pignatelli & Strettoi, 2004;Ivanova & Müller, 2006).…”
Section: Two Types Of Cbcs Expressing Voltage-gated Na + Channelssupporting
confidence: 51%
“…The existence of two subclasses of type 5 CBCs has recently been reported in the rat based on the differential immunohistochemical staining of HCN channels (Fyk-Kolodziej & Pourcho, 2007). In the mouse, morphological variability in type 5 CBCs has also been previously reported (Ghosh et al, 2004), suggesting the possibility of existing multiple subclasses of type 5 CBCs in the mouse. The results of this study, however, provide the first physiological evidence for the existence of two subclasses of type 5 CBCs in the rat, one of which expresses voltage-gated Na + channels.…”
Section: Two Types Of Cbcs Expressing Voltage-gated Na + Channelsmentioning
confidence: 89%
“…Further insights can be gained by comparing the processing of rod signals to that of cone signals. Cone signals immediately diverge to approximately 10 bipolar cell types [54][55][56][57][58]. This divergence establishes the parallel processing of visual information, a strategy that is carried forth throughout the brain.…”
Section: How Do Retinal Circuits Relay Single-photon Responses To Retmentioning
confidence: 97%
“…Haverkamp et al (2003) suggested that the primate IPL is thick enough to accommodate 20 sublayers. The number of cone bipolar cell types in the mammalian retina is usually given between 10 and 12, plus one for the rod bipolar cells (Haverkamp et al, 2003;Ghosh et al, 2004;MacNeil et al, 2004), and there is strong evidence that different bipolar cell types have different physiological properties, thus splitting the photoreceptor signals into different channels (DeVries, 2000). The number of ganglion cell types has been estimated as 13 or 14, but there is usually an unclassified remainder which could include a number of sparse or low-density cell types (Rockhill et al, 2002;Marc & Jones, 2002;Dacey et al, 2003;Yamada et al, 2005).…”
Section: Stratification Of the Iplmentioning
confidence: 99%
“…Each type branches at a characteristic depth in the IPL (Boycott & Wässle, 1991;Hartveit, 1997;Haverkamp et al, 2003;Ghosh et al, 2004;MacNeil et al, 2004) while the rod bipolar cells terminate in sublamina 5 (Young & Vaney, 1991;Massey & Mills, 1999). The division of the IPL is functional such that OFF bipolar cells terminate in the upper half, sublamina a, while ON bipolar cells, including the rod bipolar cell, terminate in sublamina b. Ganglion cells also obey these stratification rules so that OFF ganglion cells branch in sublamina a, ON ganglion cells branch in sublamina b, and ON/OFF ganglion cells are bistratified with branches in both a and b (Famiglietti & Kolb, 1976;Bloomfield & Miller, 1986;Amthor et al, 1989a,b).…”
Section: Introductionmentioning
confidence: 99%